2015
DOI: 10.1002/adma.201405565
|View full text |Cite
|
Sign up to set email alerts
|

Star‐Shaped Crystallographic Cracking of Localized Nanoporous Defects

Abstract: On self-assembled monolayer-covered Cu-Au substrates, localized volume shrinkage at initial dealloying sites leads to cracks within the attacked regions. It is started from well-controlled surface structures to gain fundamental insights in the driving mechanisms of localized corrosion and crack formation. Both the crack density and the crack morphology are critically dependent on surface orientation, crystallography, and inhibitor molecule species.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
16
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 25 publications
(23 citation statements)
references
References 50 publications
1
16
0
Order By: Relevance
“…In the wrought sample strained to 25% yield (Figure 16a), although few fine dimples exist, the fractography predominately shows intergranular fracture; Figure 16b shows the grain boundaries have been attacked. This type of failure is caused by elemental depletion at the grain boundary or weakening of the grain boundaries from oxidation, chemical attack, or embrittlement [17,27,[46][47]. Figure 17a,b also shows additional transgranular fracture.…”
Section: Fractographymentioning
confidence: 99%
See 4 more Smart Citations
“…In the wrought sample strained to 25% yield (Figure 16a), although few fine dimples exist, the fractography predominately shows intergranular fracture; Figure 16b shows the grain boundaries have been attacked. This type of failure is caused by elemental depletion at the grain boundary or weakening of the grain boundaries from oxidation, chemical attack, or embrittlement [17,27,[46][47]. Figure 17a,b also shows additional transgranular fracture.…”
Section: Fractographymentioning
confidence: 99%
“…Various studies have also shown that the stress corrosion cracking behavior of aluminum alloys in chloride environments is largely dependent on the specific immersion conditions [18,19,[44][45][46]. Additionally, precipitates can cause areas of localized corrosion because of differences in corrosion potential as compared with surrounding areas, resulting in hydrogen evolution, promoting SCC [7][8][9][10]17,[48][49]. The build-up of hydrogen can eventually embrittle the material and cause cracking [11][12][13].…”
Section: Stress Corrosion Crackingmentioning
confidence: 99%
See 3 more Smart Citations